Strategi Pemasaran Keripik Pisang Melalui Analisis SWOT Di CV. Sahabat Pangan - Bora Lamunde, Yakobus; Puri Nurani , Maria; Pungky D.H, Johanes (Fakultas Pertanian, 2023)
The background of the author doing this research is based on the problems that are often found in fruit agricultural products which generally do not last long and have properties that are easily damaged if stored in fresh form, one of which is bananas. Bananas are the most consumed fruit by households. To extend the shelf life of bananas so as to add economic value, bananas can be processed into snack products, namely banana chips. Banana chips are one of the processed bananas that are thinly sliced and then fried. This research was conducted at CV. Sahabat Pangan Klayatan, Bandungrejosari Village, Sukun District, Malang City as one of the home industries that produces banana chips. This study aims to determine the strengths, weaknesses, opportunities, threats and choose one of four strategies, namely thestrategy Aggressive SO (Strengths, Opportunities), ST Diversification strategy (Strengths, Threats), WO Turnaround strategy (Weaknesses, Opportunities), and Defensive strategies. WT (Weaknesses, Threats) to formulate marketing strategies on CV. Sahabat Pangan through SWOT analysis (Strengths, Weaknesses, Opportunities and Threats). The research method uses descriptive data collection techniques through observation, interviews, literature studies and the internet. The data analysis technique used is a qualitative descriptive analysis technique. The results of the calculation of the score on the SWOT analysis diagram are known to be the position of IFAS X (Strengths- Weaknesses) and EFAS Y (Opportunities-Threats), then it is known that the X coordinate point of 0.55 is the IFAS coordinate point and the Y coordinate point of -0.47 is the EFAS coordinate point. Then it is known that the alternative strategy used is thestrategy diversification ST (Strengths, Threats) by utilizing strengths to minimize existing threats. then there is the addition of strategic priorities, namely thestrategy diversification concentric. Thestrategy diversification concentricaims to prioritize what are the main strengths and threats of CV. Sahabat Pangan